2021
DOI: 10.1002/hep4.1747
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol‐Associated Liver Disease Before and After COVID‐19—An Overview and Call for Ongoing Investigation

Abstract: The Coronavirus Disease-2019 (COVID-19) pandemic has exacted a heavy toll on patients with alcohol-associated liver disease (ALD) and alcohol use disorder (AUD). The collective burden of ALD and AUD was large and growing prior to the COVID-19 pandemic. There is accumulating evidence that this pandemic has had a large direct effect on these patients and is likely to produce indirect effects via delays in care, psychological strain, and increased alcohol use. Now a year into the pandemic, it is important that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 43 publications
0
41
0
2
Order By: Relevance
“…Collectively, these data paint a bleak picture and highlight the immense current and future burden of morbidity and mortality precipitated by COVID-19-associated alcohol consumption [124]. This should provide additional impetus to urgently re-establish alcohol support services and to implement evidence-based population-level interventions such as minimum unit pricing and taxation of alcohol [125,126], which is also a key consideration in the EASL Lancet Liver Commission [127].…”
Section: Impact On Harmful Alcohol Use and Alcohol-related Liver Diseasementioning
confidence: 98%
See 1 more Smart Citation
“…Collectively, these data paint a bleak picture and highlight the immense current and future burden of morbidity and mortality precipitated by COVID-19-associated alcohol consumption [124]. This should provide additional impetus to urgently re-establish alcohol support services and to implement evidence-based population-level interventions such as minimum unit pricing and taxation of alcohol [125,126], which is also a key consideration in the EASL Lancet Liver Commission [127].…”
Section: Impact On Harmful Alcohol Use and Alcohol-related Liver Diseasementioning
confidence: 98%
“…Lastly, simulation modelling in the United States has estimated that a single year of increased alcohol consumption during the pandemic may result in 8,000 additional deaths from ALD, 18,700 cases of decompensated cirrhosis, 1,000 cases of HCC, and 8.9 million disability-adjusted life years between 2020 and 2040 [ 123 ]. Collectively, these data paint a bleak picture and highlight the immense current and future burden of morbidity and mortality precipitated by COVID-19-associated alcohol consumption [ 124 ]. This should provide additional impetus to urgently re-establish alcohol support services and to implement evidence-based population-level interventions such as minimum unit pricing and taxation of alcohol [ 125 , 126 ], which is also a key consideration in the EASL Lancet Liver Commission [ 127 ].…”
Section: Effects Of the Covid-19 Pandemic On Incidence And Management...mentioning
confidence: 99%
“…The aging of China's population is a major contributor to the epidemic of diabetes in China, with older adults representing one of the fastest-growing segments of the patient population with diabetes. [2][3][4][5] Thus, comprehensive actions are needed to address China's national diabetes burden from health, economic, and social perspectives. In Reply Dr Tu and colleagues raise some methodological questions about the field surveys that collected the data used in our study 1 and how to interpret some of the reported results.…”
Section: Supplemental Contentmentioning
confidence: 99%
“…Expanding the LT indication for acute alcoholic hepatitis in recent years93 94 has certainly contributed to this shift in the epidemiology of LT waiting lists. In the COVID-19 era, aggravating factors such as the psychological burden and delays in healthcare have contributed to an increase in alcohol use disorder, as suggested by some reports 95…”
Section: Covid-19 and Liver Transplantmentioning
confidence: 99%